IDENTIFIKASI NEMATODA DI PERKEBUNAN KELAPA SAWIT PTPN V SEI PAGAR - Darmawan, Arbi; Arminudin, Ahmad Taufiq; Rahmadani, Elfi (Jurnal Agroteknologi, 2024)
Nematodes are plant pest organisms from the phylum Nemathelmithes which are composite in nature and attack various types of main crops such as oil palm so that they can cause varying losses. The heaviest losses usually occur at the end of the rainy season and the first 2-3 months of the dry season. This research aims to identify nematodes associated in soil with oil palm plants at the PTPN V Sei Pagar Oil Palm Plantation. The research was carried out in October – December 2023 in the form of surveys and observations using experimental methods containing the results of observations of nematode morphology. Root and soil samples were taken at PTPN V Sei Pagar, nematode extraction used a modified Baerman funnel method and identification was carried out at the Pathology, Entomology, Microbiology and Soil Science Laboratory, Faculty of Agriculture and Animal Husbandry, State Islamic University of Sultan Syarif Kasim Riau. The results of the research showed that the nematode genera found at PTPN V Sei Pagar in two divisions and different planting years were 4 genera, namely Helicotylenchus, Mylonchulus, Rhabditis and Aphelenchus